2005
DOI: 10.3354/meps287209
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic isopod Anilocra apogonae, a drag for the cardinal fish Cheilodipterus quinquelineatus

Abstract: Cymothoid isopods Anilocra apogonae are regular ectoparasites of the cardinal fish Cheilodipterus quinquelineatus on the Great Barrier Reef. To determine whether this large isopod, attached to the head of the fish, affects the physiology and behaviour of its host, we conducted morphological measurements to obtain a condition index and several laboratory experiments on fish with and without isopods. The condition index did not vary between parasitised and non-parasitised wild fish. However, we found that parasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
3
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 27 publications
(30 reference statements)
2
45
3
2
Order By: Relevance
“…The authors attributed this increase in energetic cost to the destabilizing effect of the asymmetrically attached parasite rather than to any physiological effects of parasitism. Indeed, they found that parasitized fishes used their pectoral fins more while at rest, presumably in order to maintain stability [5]. Our results suggest otherwise, because SMR did not increase when a model parasite was added, and we did not observe any change in pectoral fin beat frequency when fish were at rest (S. A. Binning 2012, unpublished data).…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…The authors attributed this increase in energetic cost to the destabilizing effect of the asymmetrically attached parasite rather than to any physiological effects of parasitism. Indeed, they found that parasitized fishes used their pectoral fins more while at rest, presumably in order to maintain stability [5]. Our results suggest otherwise, because SMR did not increase when a model parasite was added, and we did not observe any change in pectoral fin beat frequency when fish were at rest (S. A. Binning 2012, unpublished data).…”
Section: Discussionsupporting
confidence: 46%
“…Parasitized fish, however, continued to consume an average of 24 per cent more oxygen on average when at rest than fish in the other three treatments. Ostlund-Nilsson et al [5] found similar increases in the resting metabolic rate of the cardinalfish, Cheilodipterus quinquelineatus, parasitized by a congeneric isopod, Anilocra apogonae. The authors attributed this increase in energetic cost to the destabilizing effect of the asymmetrically attached parasite rather than to any physiological effects of parasitism.…”
Section: Discussionmentioning
confidence: 82%
“…The first stage (mancae or early juvenile I stage) consists of a short phase as free-living organisms with good swimming ability, after which they need to find a fish to take their first meal (within 1 to several days) or they die (Tsai & Dai 1999, Mladineo 2003, Fogelman & Grutter 2008. Upon finding a suitable host, they initiate feeding, generally on blood and macerated tissues (mucus, epithelium and subcutaneous tissues) (Colorni et al 1997, BunkleyWilliams & Williams 1998, Horton & Okamura 2003, Östlund-Nilsson et al 2005. They attach to skin, fins, branchial or buccal cavities, or burrow into the musculature of fishes.…”
Section: Introductionmentioning
confidence: 99%
“…The parasites also affected the stability of their host requiring them to expend more energy just to keep upright (Ö stlund-Nilsson et al 2005). These isopods are potentially economically important parasites as they have been shown to cause detrimental effects on fish in captivity including growth inhibition, anaemia and death in smaller fish Adlard and Lester (1995).…”
Section: Resultsmentioning
confidence: 99%